Such a perfect family - Singh, Nalini, 1977- (Berkley, 2026)
"A man with a deadly past marries into the perfect, respectable family in this riveting thriller from New York Times bestselling author Nalini Singh... A woman buried. A woman broken. A woman crashed. A woman burned. And the man who knew them all. Love at first sight, a whirlwind Vegas wedding, a fairytale romance. For seventy-nine days, Tavish Advani has been the happiest man in the world-until his new life turns to ash, his wealthy in-laws' house going up in a fiery explosion. His badly injured wife lies in a coma, her family all but annihilated. Tavish thought he left the sins of his Los Angeles life behind, but it's not so easy to leave behind an investigation into the deaths of several high-profile women-all of whom he professed to love. Tragedy and death follow him no matter where he goes...but this time he knows he's innocent. Desperately trying to clear his name as the authorities zero in, he begins his own investigation into the fire-and learns that his wife's picture-perfect family may have been nothing but a meticulously constructed mirage. The truth is much darker than anything Tavish could've imagined..."-- Provided by publisher.